Biotechnological Potential of Antigens of Plague, Cholera, Tularemia and Anthrax Pathogens, Obtained at the Russian Research Institute “Microbe” - M. N. Kireev; O. V. Gromova; S. V. Borisova; S. A. Vorob’eva; V. R. Vol’nikov; R. R. Salikhov; O. A. Volokh (Проблемы особо опасных инфекций, 2024)
Russian Research Anti-Plague Institute “Microbe” of the Rospotrebnadzor develops and implements methods for obtaining and purifying biologically active substances of the causative agents of plague, cholera, tularemia and anthrax, which are used in the design of preventive and diagnostic preparations.The aim of the review is to summarize and systematize the accumulated data on the isolation, purification and assessment of antigens and toxins of plague, cholera, tularemia and anthrax pathogens. Attention is also paid to the application and prospects for using the obtained antigens for the design of medical immunobiological preparations (MIBPs). The Institute “Microbe” is a reference center for plague, hence modern immunodiagnostic drugs are necessary and in demand. Antigen-level preventive drugs against the infections listed above are also the subject of study by the institute’s staff. The main stages of isolation, purification and analysis of antigens include the selection or construction of a suitable strain; cultivation, extraction, concentration and purification of antigens and toxins using biotechnological techniques that allow for obtaining and preserving the biologically active substance of interest to the researcher. To study the antigenic activity of purified antigens, laboratory animals are involved, the immune response is recorded and analyzed, and antiserum is obtained. This is followed by the stage of investigating the physicochemical and immunobiological properties of the isolated antigen preparations and drawing up an antigen profile. The characterized antigens are used for the design of preventive and diagnostic drugs.